Students perceptions about the pedagogic strategies for teaching-learning anatomy at university Eduardo Mondlane in Mozambique - Rodrigues, Maria Alexandra Fernandes (International Journal of Research in Medical Sciences, 2020)
Background: From the need to develop a new curriculum for the medical course, changing the traditional model used for teaching Gross Anatomy it was sought to incorporate active teaching methodologies which can allow students to be more involved in the process of knowledge construction. The way in which Gross Anatomy is delivered in most Faculties of Medicine has been seen as a big challenge to the teachers and the students too as a consequence of permanent changes that are required in order to be in line with the technological development. This study aimed to explore the student's perceptions about the effectiveness of the strategies and resources, used in teaching-learning Gross Anatomy in the medical course at EMU. Methods: Data were collected using a questionnaire administrated to those medical students who attended (1st and 2nd year) Gross Anatomy subjects, in November 2018. Descriptive statistics and data content analysis were performed. The sample comprised 171 students. Results: A convergence of strategies preferred by the students involved in the study was seen. It was recognized that Gross Anatomy curriculum was designed based on the limitations of the use of cadaver dissection, with the emphasis on applied anatomy and learning in small groups using other resources, including computer assisted learning based on the 3-D Slicer software. Conclusions: It appears that the students' desire is that the teaching-learning strategies used in Anatomy classrooms at UEM might contribute to their better training for the professional challenges when graduated. They perceived that with the strategies used for teaching Anatomy, they are being very well prepared to get in an entrepreneurial, transformative profile and are able to learn more complex contents in order to provide a qualified health care to people in the performance of their future functions as doctors.